Ocean as method - Menon, Dilip M., author.
1 online resource
Keywords: "Ocean as Method presents a new way of thinking about the humanities and the social sciences. It explores maritime connections in social and humanistic research and puts forward an alternative to national histories and area studies. As global warming and rising sea levels ring alarm bells across the world, the essays in the volume argue that it is time to think through oceans to realign discourses which better understand our future. The volume: - Engages with the paradigms of oceanic narratives to identify connections between continents through trade, migration, and economic processes, thinking beyond the artificial distinctions between the Pacific, Atlantic, and Indian Oceans; - Discusses oceanic travel accounts by Muslim travelers to counter the idea that the colonial era was marked by European travel to Asia and Africa, without a counterflow of "native travel"; - Examines the connections between South Africa, South Asia, and South East Asia through histories of Indian indenture and the slave trade, and engages with the idea of the ocean and enforced movement; - Compares and connects recent scholarship in the social sciences and the humanities centering the ocean to break away from inherited paradigms which have shaped world history so far. A unique transdisciplinary collaboration, this volume will be of much interest to scholars and researchers of history, especially oceanic history, historiography, critical theory, literature, geography, and Global South studies"--